Pemanfaatan Multi-Layer Perceptron (MLP) untuk Deteksi Kanker - Firmansyah, Fahrul; Sari, Anggraini Puspita; Sugiarto, Sugiarto (Universitas Merdeka Malang, 2025)
Cancer is one of the deadliest diseases in the world. This is because patients often do not realize the presence of cancer in their bodies, leading to delayed treatment and the cancer becoming aggressive. Early diagnosis of cancer in women is necessary since the majority of cancer patients are women. One of the markers that can be used to diagnose cancer is the anti-Mullerian hormone, accompanied by other indicators such as lifestyle, BMI, and others. Early diagnosis can utilize the Multi-Layer Perceptron (MLP) algorithm, which is currently a rapidly developing technology. By using the MLP algorithm, an accuracy of 84% is achieved on the training data and test data, with a training-to-testing data ratio of 65:35.